Digitalisasi Informasi dan Pembelajaran di SD Muhammadiyah 3 Parepare - Syawal, Syawal; Patahuddin, Patahuddin; Kurniawan, Edy; Abdullah, Muhaimin; Idris, Radiah Azizah; Syahrir, Astriyani (STMIK Royal, 2024)
Digital-based learning is the biggest obstacle faced by partner schools. This has an impact on the accessibility of learning materials and limited information. Therefore, this PKM aims to develop a prototype website for elementary schools to improve the quality and accessibility of education in partner schools. The research method used is a design-based research approach consisting of two semesters. The first semester is used to design and develop a prototype of the school's website, while the second semester is focused on analyzing and testing its effectiveness. The limitation of this study lies in creating a prototype school website that can support the teaching and learning process in schools through digital-based teaching media. The results of this development research are a prototype of a school website that is ready to be tested. The prototype of the school website developed is expected to be a valuable medium for schools, students, and parents to support a more effective and efficient learning process. Thus, this research is expected to open the door to a more inclusive and quality education for all children in Parepare. Keywords: Digital-based open media; Design-based research prototype; Learning effectiveness; Basic education; Web-based school;Pembelajaran berbasis digital menjadi kendala terbesar yang dihadapi oleh sekolah mitra. Hal ini berdampak pada aksesibilitas materi pembelajaran dan informasi yang terbatas. Oleh karena itu, PKM ini bertujuan untuk mengembangkan sebuah prototipe website untuk sekolah dasar sebagai solusi untuk meningkatkan kualitas dan aksesibilitas pendidikan di sekolah mitra. Metode penelitian yang digunakan adalah pendekatan design based research, yang terdiri dari dua semester. Semester pertama digunakan untuk merancang dan mengembangkan prototipe website sekolah, sementara semester kedua difokuskan pada analisis dan pengujian efektivitasnya. Batasan kajian ini terletak pada pengembangkan prototipe website sekolah yang dapat memberikan dukungan terhadap proses belajar mengajar di sekolah melalui media ajar berbasis digital. Hasil dari penelitian pengembangan ini berupa prototipe website sekolah yang siap untuk diujicobakan. Prototipe website sekolah yang dikembangkan diharapkan dapat menjadi media yang bermanfaat bagi sekolah, siswa, dan orang tua dalam mendukung proses pembelajaran yang lebih efektif dan efisien. Dengan demikian, penelitian ini diharapkan mampu membuka pintu menuju pendidikan yang lebih inklusif dan berkualitas bagi semua anak di Kota Parepare.Kata kunci: Media ajar berbasis digital; Design based research Prototipe; Efektivitas pembelajaran; Pendidikan dasar; Web-based school;